ELECTROMAGNETIC AND GRAVITO-MAGNETIC MULTIPLICATIVE THERMORESONANCES OF COHERENT HELICON FORMS OF THE MOTION OF THE HETEROPHASE PLASMA MEDIUM OF THE CENTRAL-ANTISYMMETRIC COMPLEX SPACE. DISCONTINUOUS THERMOMAGNETOPLASMONIC NATURE OF MASS, CHARGE, SPIN AND MAGNETIC MOMENT - ZASPA, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
A physical model of the centrally antisymmetric complex space as a heterophase plasma medium with open and closed subsystems separated by rotational contact gaps is proposed. Thermal fluctuations of such an environment generate uncompensated charge carriers, while the transition from a non-inertial frame of reference associated with discontinuities to a system of the center of symmetry determines the presence of a magnetic field necessary for organizing the movement of the corresponding helicon structures of the electromagnetic and gravitomagnetic fields. The opposite direction of the dominant energy cascades and relaxation processes in open and closed subsystems, the contact union of which forms the mass, charge, spin, and magnetic moment of micro- and macroparticles of matter, is noted. Based on the spectral analysis of collider resonances, a multi-scale complex lepton structure of the proton and the rest of the baryons was established. It is shown that the outer gap radii of the triplet 2e-shell of the proton are two orders of magnitude larger than those that are usually used. It was found that, similar to the structure of the Sun and stars, baryons have a strong concentration of mass towards the center - in the form of a larger complex polymuon core and an inner compact tau core. Hybrid forms of electromagnetic and gravitomagnetic helicon motion structures in technical, space and biological systems are considered. The threefold multiplicative nature of helicon resonances was confirmed and their parameters were calculated in natural systems of various scales. A two-way limitation of resonance spectra is established, the upper limit of which corresponds to the autocyclotronic thermal resonance of uncompensated charge carriers and extended spectral clusters. It is shown that the formation of stable forms of matter is carried out due to self-looping of forward and reverse energy cascades in contact-connected open and closed subsystems. Thermally conditioned transitions between localized and jet forms of movement of helicon structures are considered. The important role of the internal coherence of such structures is noted, the violation of which destroys and transforms the latter. Catastrophic buffeting regimes of helicon thermal resonances in technical and biological systems are analyzed. The obtained results refute completely false physical standards (SM, Lambda-CDM, standard model of the Sun), artificially implemented without taking into account the central antisymmetry and the discontinuous structure of the complex space.